(untitled) (Eurasian Research Bulletin, 2023)
Business classification is an important aspect of tax policy and tax administration, as it allows governments to design targeted tax measures and implement effective tax collection processes. This abstract examines the criteria used in the classification of business entities and their importance in the further improvement of tax policy and management. Therefore, it is essential to address these issues and develop effective measures to improve the taxation practice for SMEs. This abstract serves as an introduction to the discussion of the key aspects related to taxation of SMEs and ways to enhance the compliance and efficiency of the tax system for these businesses